Investigating the Development of Urban Space in the face of Environmental Hazards (Case Study of Noor County) - Hossein Sharifi; Mehrdad Ramezanipour; Leila Ebrahimi (تحقیقات کاربردی علوم جغرافیایی)
Today, human settlements around the world are exposed to natural hazards for a variety of reasons. These risks, which bring with them a lot of human and financial losses, require preventive measures. The purpose of this study is to investigate the development of urban space in order to deal with environmental hazards in Noor city. The method of this research is also descriptive. Data collection is using library and documentary studies and questionnaires. In order to analyze the questionnaires using ANP method and fuzzy logic method, evaluate each of the criteria and determine their importance coefficients. Based on the results, spatial assessment was performed using ArcGis software and hazard zones were identified. According to the results of risk potential zoning, the northern and southern areas of the city have the highest risk potential. To predict the development of residential areas, the combined Markov chain model and cellular automation were used. The results showed that the continuous expansion of built areas in recent decades has caused rapid changes in land use and the built areas of the city has increased from 2.43% of the total area in 2010 to 3.68% in 2019. The results also showed that regardless of the natural hazards, the built-up areas will increase and as a result of urbanization, the built-up areas will be more prone to high-risk lands. However, if sustainable development policies are fully implemented, cities and built-up areas will be able to maintain their development spaces from high-risk areas for the benefit of the city and its residents.